Impact of ICT On the Management of MSMES for Their Digital Competence in Business: A Review of Scientific Literature 2000 – 2020 - Leonardo Carreño-Machero; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
Micro, small and medium-sized enterprises are present all over the world and play a key role in the economy of the countries where they operate. Today, large companies use Information Technology and Communications to optimize their processes. The methodology that this study used was the systematic review of scientific literature, which collected 72 articles from the following databases: IEEE Xplore, EBSCO Host, Scielo, ScienceDirect and Taylor&Francis. Showing the strategies for the adoption of Information Technology and Communications in micro, small and medium-sized enterprises are: the managers of the organizations should acquire ICTs according to the needs of the company, a good infrastructure must be in place for the arrival of new technologies and personnel must be trained, together with the barriers that these enterprises face when trying to adopt Information Technology and Communications are: the money, lack of qualified personnel, inadequate ICT infrastructure and owners' unwillingness to make organizational changes.
Keywords: ICT and SME; adopt and barriers; strategies ICT and SME; digital transformation; systematic review.